The Effect of 12 and 24-Hour Blue Lighting on Performance and Feeding Behaviour of Broiler Chickens - Diah Reni Asih; Sri Harimurti; Wihandoyo Wihandoyo (Buletin Peternakan, 2018)
This study was conducted to assess the effects of the 12 and 24 hours blue lighting on the performance of broiler chickens. This study used 2,700 broiler chickens that were divided into three treatments which are: control lighting (K) with conventional light used by farmers, 12-hours blue lighting (B12), and 24-hours  blue lighting (B24). Each treatment was repeated three times and consisted of 300 broiler chickens each. The parameters observed were feeding behaviour including the feeding duration, feeding frequency, and broiler chickens performance. The results showed that broilers treated with the B24 and B12 lighting have longer feeding duration (P<0.05), lower feeding frequency (P<0.05), higher body weight gained (P<0.05), and lower feed conversion (P<0.05) when compared to those of chickens with K lighting. The conclusion of this study showed that continuous 24-hours blue lighting (B24) caused longer feeding duration  and lower feeding frequency and the treatment of B24 and B12 lighting gave better benefits than control lighting.